2011
DOI: 10.1063/1.3582134
|View full text |Cite
|
Sign up to set email alerts
|

Absolute measurements of x-ray backlighter sources at energies above 10 keV

Abstract: Line emission and broadband x-ray sources with x-ray energies above 10 keV have been investigated using a range of calibrated x-ray detectors for use as x-ray backlighters in high energy density (HED) experiments. The conversion efficiency of short-and long-pulse driven Mo and Ag line-emission backlighters at 17 and 22 keV was measured to investigate the crossover region between short-and long-pulse conversion efficiency. It was found that significant 17 and 22 keV line emissions were observed using a 3 x, 1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…The ripple growth is measured by face-on radiography. In order to probe the thickness of our Ta sample, we developed a high energy backlighter using the high-intensity short pulse lasers [11,12]. For our Omega experiment, we found that 22 keV energy was optimal to produce the best contrast from our ripples.…”
Section: Introductionmentioning
confidence: 99%
“…The ripple growth is measured by face-on radiography. In order to probe the thickness of our Ta sample, we developed a high energy backlighter using the high-intensity short pulse lasers [11,12]. For our Omega experiment, we found that 22 keV energy was optimal to produce the best contrast from our ripples.…”
Section: Introductionmentioning
confidence: 99%
“…We note that pump laser energy is 30 times larger at NIF than at OMEGA and that the ratio of backlighter fluences exceeds that factor due to the higher backlighter electron temperature at NIF 41 . Consequently, ED-XRD is also viable at NIF where the higher backlighter fluence may allow a substantial reduction in solid angle subtended by an HOPG spectrometer, compared to present calculations.…”
Section: Resultsmentioning
confidence: 99%
“…One readily available broadband source in laser shock experiments is the thermal spectrum from a laser-imploded polymer shell, usually filled with H 2 -D 2 gas 41,42 . In Fig.…”
Section: Iia Source and Targetmentioning
confidence: 99%
“…1 and has been described previously 4,7,8 . A set of 29-42 beams was used to drive an implosion in a hollow plastic capsule with 980 µm diameter and a 9 µm thick wall to produce a bright, short (∼150 ps) burst of broadband x-rays (5-25 keV) generated by bremsstrahlung radiation when the capsule material stagnates at the center 7,8 . A planar shock wave is created in the Ta crystal by direct laser illumination using a single 3ω beam with a distributed phase plate to smooth the spot profile and a 1-4 ns square pulse shape.…”
Section: Experimental Techniquementioning
confidence: 99%